XOmB: an Exokernel for Modern 64-bit, Multicore Hardware - Larkby-Lahet, James; Madden, Brian A.; Wilkinson, Dave; Mosse, Daniel (Anais do Workshop de Sistemas Operacionais (WSO); 2010: Anais do VII Workshop de Sistemas Operacionais, 2010)
We describe XOmB, an exokernel being developed to exploit the features of modern hardware. Specifically we discuss the use of large 64-bit virtual address spaces to provide a hybrid of segmentation and paging. This abstraction allows us to expose files and memory-mapped devices using the same mechanism. We also describe current work to develop a multicore scheduling mechanism that balances efficency and userspace flexibility.